How do reactive oxygen species and calcium trigger mitochondrial membrane permeabilisation? - Tajeddine, Nicolas (Biochimica et biophysica acta, 2016)
Mitochondrial membrane permeabilisation (MMP) is classically considered as a point of no return in several forms of cell death and is involved in numerous diseases such as cancer, neurodegenerative disorders or ischemia/reperfusion injuries. Many studies established that reactive oxygen species (ROS) and Ca2+ were the prominent inducers of MMP. However, the mechanisms connecting ROS and Ca2+ to the players of MMP are still a matter of debate. The aim of this review is to summarise the various studies related to the mechanisms of ROS- and Ca2+-induced MMP. Several lines of evidence suggest that ROS and Ca2+ cooperate to induce MMP but the molecular details of the ROS–Ca2+-MMP network remain controversial. We then discuss recent data depicting this topic. Cytotoxic stimuli may be transduced within the cell by ROS and Ca2+ increases. In most models, Ca2+ and ROS can cooperate to induce MMP. Moreover, several data suggest that MMP increases mitochondrial Ca2+ and ROS which therefore amplify the cytotoxic signal. Intriguingly, many reports have identified players of MMP as direct ROS targets. On the contrary, direct targets of Ca2+ remain elusive. At the same time, the mechanisms by which mitochondrial Ca2+ overload induces ROS generation are well documented. Upon these observations, we hypothesise that Ca2+ cannot directly induce MMP and requires ROS production as a mandatory step. Given the importance of Ca2+- and ROS-induced MMP in diseases, we expect that a better understanding of this process will lead to the development of novel therapies. •Mitochondrial membrane permeabilisation (MMP) is a crucial step leading to cell death.•In most models, ROS and mitochondrial Ca2+ cooperate to induce MMP.•ROS directly target several components involved in MMP.•However, the mechanisms by which mitochondrial Ca2+ induces MMP remain obscure.•Ca2+ might require mitochondrial ROS generation as a mandatory step to trigger MMP.